Answer: ![y-1=\dfrac32(x+3)](https://tex.z-dn.net/?f=y-1%3D%5Cdfrac32%28x%2B3%29)
Step-by-step explanation:
Slope of a line passes through (a,b) and (c,d) = ![\dfrac{d-b}{c-a}](https://tex.z-dn.net/?f=%5Cdfrac%7Bd-b%7D%7Bc-a%7D)
In graph(below) given line is passing through (-2,-4) and (2,2) .
Slope of the given line passing through (-2,-4) and (2,2) =![\dfrac{-4-2}{-2-2}=\dfrac{-6}{-4}=\dfrac{3}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7B-4-2%7D%7B-2-2%7D%3D%5Cdfrac%7B-6%7D%7B-4%7D%3D%5Cdfrac%7B3%7D%7B2%7D)
Since parallel lines have equal slope . That means slope of the required line would be .
Equation of a line passing through (a,b) and has slope m is given by :_
(y-b)=m(x-a)
Then, Equation of a line passing through(-3, 1) and has slope = is given by
![(y-1)=\dfrac32(x-(-3))\\\\\Rightarrow\ y-1=\dfrac32(x+3)](https://tex.z-dn.net/?f=%28y-1%29%3D%5Cdfrac32%28x-%28-3%29%29%5C%5C%5C%5C%5CRightarrow%5C%20y-1%3D%5Cdfrac32%28x%2B3%29)
Required equation: ![y-1=\dfrac32(x+3)](https://tex.z-dn.net/?f=y-1%3D%5Cdfrac32%28x%2B3%29)
For this case we have the following definitions:
A function is even if, for each x in the domain of f, f (- x) = f (x). The even functions have reflective symmetry through the y-axis.
A function is odd if, for each x in the domain of f, f (- x) = - f (x). The odd functions have rotational symmetry of 180º with respect to the origin.
We then have the following function:
![f (x) = 9 - 4x ^ 2](https://tex.z-dn.net/?f=%20f%20%28x%29%20%3D%209%20-%204x%20%5E%202%20%20)
Applying the definitions we have:
![f (-x) = 9 - 4 (-x) ^ 2\\f (-x) = 9 - 4 (x) ^ 2\\f (-x) = f (x)](https://tex.z-dn.net/?f=%20f%20%28-x%29%20%3D%209%20-%204%20%28-x%29%20%5E%202%5C%5Cf%20%28-x%29%20%3D%209%20-%204%20%28x%29%20%5E%202%5C%5Cf%20%28-x%29%20%3D%20f%20%28x%29%20%20)
Answer:
The function is not odd because it is fulfilled:
![f (-x) = f (x)](https://tex.z-dn.net/?f=%20f%20%28-x%29%20%3D%20f%20%28x%29%20%20)
Therefore, the function is even.
The answer is $41.44.
You take $895× 4.63%= $41.4385.
It is 4 because 3 times 4 equals 12
--------------------------------------------------
Define x :
--------------------------------------------------
Let Cheryl be x years old.
Cheryl = x
Lisa = x + 6
--------------------------------------------------
In two years time:
--------------------------------------------------
Cheryl = x + 2
Lisa = x + 8
--------------------------------------------------
Lisa will be twice as old as Cheryl :
--------------------------------------------------
x + 8 = 2(x + 2)
--------------------------------------------------
Solve x :
--------------------------------------------------
x + 8 = 2(x + 2)
x + 8 = 2x + 4
x = 4
--------------------------------------------------
Find their age :
--------------------------------------------------
Cheryl = x = 4
Lisa = x + 6 = 4 + 6 = 10
--------------------------------------------------
Answer: Lisa is 10 years old now.
--------------------------------------------------